2021
DOI: 10.1002/adem.202100221
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Poly (N‐Isopropylacrylamide)/Polycaprolacton Nanofibrous Scaffolds for Controlled Release of Antibiotics

Abstract: Smart antibacterial materials capable of releasing antibiotic drugs upon exposure to external triggers are highly desired for various medical applications. Herein, the fabrication of thermosensitive drug‐loaded core−shell nanofibers using the electrospinning technique combined with in situ UV photopolymerization is reported on. The electrospinning method is used for shaping the core structure comprising biodegradable polymer polycaprolactone (PCL). The PCL fibers are coated with the temperature‐responsive poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Various hydrogel-based dosage forms based on TSHs have been developed to better target and control the current systems. [111] In the ophthalmic field, the low bioavailability of eye drops due to rapid clearance action induced by tear dilution and the lacrimal drainage system represents a limitation. Luo et al [112] demonstrated effective topical treatment of dry eye disease (DED) through a mucoadhesive drug delivery system based on TSHs.…”
Section: Thermosensitive Hydrogels In Drug Delivery Systems (Dds) App...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various hydrogel-based dosage forms based on TSHs have been developed to better target and control the current systems. [111] In the ophthalmic field, the low bioavailability of eye drops due to rapid clearance action induced by tear dilution and the lacrimal drainage system represents a limitation. Luo et al [112] demonstrated effective topical treatment of dry eye disease (DED) through a mucoadhesive drug delivery system based on TSHs.…”
Section: Thermosensitive Hydrogels In Drug Delivery Systems (Dds) App...mentioning
confidence: 99%
“…Various hydrogel‐based dosage forms based on TSHs have been developed to better target and control the current systems. [ 111 ]…”
Section: Biomedical Emerging Applications Of Poly(n‐isopropylacrylami...mentioning
confidence: 99%
“…[ 120 ] In another research, a PCL nanofibrous surface was functionalized by coating the fibrous matrix with thermo‐responsive PNIPAAm crosslinked in situ under UV light. [ 121 ]…”
Section: Thermoresponsive Electrospun Fibersmentioning
confidence: 99%
“…Wound dressings made of nanofiber polymers with antibacterial effects and skin regeneration capabilities are good choices for preventing wound infection and speeding wound healing. [183][184][185][186][187][188][189][190][191][192] Antimicrobial agents have been applied to nanofibers to boost their antimicrobial activity. Antimicrobial substances, both inorganic and organic, have been used to achieve this aim.…”
Section: Polymer Advantages and Limitationsmentioning
confidence: 99%